1α,6β,7β,14β,15β-Pentahydroxy-7α,20-epoxy-ent-kaur-16-ene - Feng, Chuang (International Union of Crystallography, 2009)
The title compound, enmenol, C(20)H(30)O(6), a natural ent-kaurane diterpenoid, comprises five fused rings, four of which are six-membered. Cyclohexane ring A adopts a chair conformation, rings B and C adopt boat conformations, while ring D has an envelope conformation, and two intramolecular O—H⋯O interactions occur. In the crystal, intermolecular O—H⋯O hydrogen bonds generate a two dimensional network.